On the Derived Length of a Finite Group with Complemented Subgroups of Order p^2 - Knyagina, V. N.; Monakhov, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
It is shown that a finite group with complemented subgroups of order p^2 is soluble for all p and its derived length does not exceed 4.